PENGARUH KOMPENSASI KOMITMEN DAN KEPUASAN KERJA GURU TERHADAP PENINGKATAN MUTU PEMBELAJARAN DENGAN LOKASI PENELITIAN DI SMPN PANTE CEUREUMEN ACEH BARAT - Umi Kalsum; Suparta Rasyid; Said Mulyadi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The aims of this research are (1) to analyze the effect of compensation on the quality of learning at SMPN Pante Ceureumen West Aceh; (2) to analyze the influence of teacher work commitment on the quality of learning at SMPN Pante Ceureumen West Aceh; (3) to analyze the effect of teacher job satisfaction on the quality of learning at SMPN Pante Ceureumen West Aceh; and (4) to analyze the influence of compensation, commitment, and job satisfaction of teachers on the quality of learning at SMPN Pante Ceureumen West Aceh. This research uses a quantitative method with a descriptive approach, a population of 23 people, a sample of 23 people, and a simple random sampling technique using Sugiyono's sampling technique. The data collection technique was carried out using a Likert scale questionnaire and multiple linear regression data processing techniques. The research findings were partially obtained: (1) compensation did not have a positive influence on the quality of learning with a coefficient of 0.461, or 46.1% (in percentage), and hypothesis testing produced a calculated T value of 0.752, which was smaller than the T table value of 2.093. This shows that the compensation variable has no effect on the quality of learning. (2) Commitment has a positive influence on the quality of learning with a coefficient of 0.008 or 0.08% (in percentage). Hypothesis testing produces a calculated T value of 2.984, which is greater than the T table value of 2.093. (3) Teacher job satisfaction has a positive influence on the quality of learning with a coefficient of 0.463, or 46.3% (in percentage). Hypothesis testing produces a calculated T value of 0.748, which is smaller than the T table value of 2.093. Meanwhile, simultaneously, it was found that teacher compensation, commitment, and job satisfaction had a positive influence on the quality of learning, with a constant value of 8.670. The findings in this research have practical implications, namely that teacher compensation, commitment, and job satisfaction have implications for improving the quality of learning at SMPN Pante Ceureumen, West Aceh Regency. Advice to all school principals: compensation should be given more attention and given for the welfare of educators and education staff. In this way, the hope is that teacher performance will increase and be maximized. A teacher should have organizational commitment and high work enthusiasm so that the vision and mission targets schools can be easily achieved, and every teacher must have and maintain job satisfaction so that they remain enthusiastic in carrying out their duties and responsibilities as educators. It is hoped that this will have an impact on improving teacher performance and the quality of education nationally.